PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SEJARAH DI KELAS X SMA N 1 XIII KOTO KAMPAR - nurhafizah, Yuliana; Ibrahim, Bedriati; ', Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The learning model Picture And Picture is a model that uses an image in the form of pieces to then paired and sorted into a complete picture, this model can motivate students to study the subjects of history is easy to observe, as well as enhancing memory so that the absorption material more quickly overpowered and at the time of the evaluation results would be better. By applying this model can help to more active involvement of the student so that students more easily understand the material they receive and to help improve the mastery of the subject matter so that can improve result student learning outcomes. The purpose of this research is 1) to determine the level of activity of teachers with penerpan learning model Picture And Picture, 2) to determine the activity of learners with the application of Picture And Picture, 3) to determine how much an increase in the study of students with learning model Picture And pictur. This study was conducted 2 cycles. Subjects in this study were all students of class X SMA N 1 XIII Koto Kampar totaling 34 technical analysis of the data in this study using quantitative descriptive. The results showed that the activity of a teacher for two cycles has risen 17 with enough categories and 21 in both categories in the first cycle and 23 with very good categories and 24 very well in the second cycle. Activities of students has increased by a score of 335 with less category and 444 with enough categories in the first cycle, a score of 674 with both categories and 907 with excellent category on the second cycle. While learning the test results of students has increased during two cycles of the first cycle with an average value of 72.35 increased to 86.47 in the second cycle, it can be disimpulakan that using models Picture And Pictur can increase the activity of teachers, student activities and results test subjects learn the history of class X SMA N 1 XIII Koto Kampar.Keywords: Learning Model Picture And Picture, Learning, Learning Outcomes